The Transcription Factor BrNAC19 Acts as a Positive Regulator of the Heat Stress Response in Chinese Cabbage - Shuai Yuan; Xiaoping Yong; Yuxin Lu; Yuxin Lei; Weijian Li; Qiuli Shi; Xiuhong Yao (Horticulturae)
The frequent occurrence of excessive heat events driven by global warming poses a great threat to plant growth and food security. To survive in heat stress (HS) environments, plants have evolved sophisticated response mechanisms, and the transcriptional network that controls the expression levels of HS-inducible genes serves as an essential component of this process. NAC (NAM, ATAF1/2, and CUC2) transcription factors (TFs) play key regulatory roles in the abiotic stress responses of plants. However, the functional roles of NAC TFs in the heat stress response of Chinese cabbage remain elusive. In the present study, we identified the Brassica rapa NAC family transcription factor BrNAC19 as a close homologue of Arabidopsis NAC019 and found that it serves as a positive regulator of the HS response. BrNAC19 displayed inducible gene expression in response to HS, and its subcellular localization showed that it was localized in the nucleus. Heterologous expression of BrNAC19 significantly enhanced the heat tolerance of plants and reduced the accumulation of reactive oxygen species (ROS) under HS conditions. Furthermore, our results demonstrated that BrNAC19 directly targeted and promoted the expression of superoxide dismutase 1 (CSD1) and catalase 2 (CAT2), two antioxidant-enzyme coding genes in Chinese cabbage. Altogether, our results suggest that BrNAC19 enhances heat stress tolerance by positively regulating the expression of genes involved in the HS response and ROS scavenging and exhibits potential as a target gene in Chinese cabbage breeding to increase heat stress tolerance.